Investigating the Critical Factors Affecting Citizens’ e-Government Adoption in South Africa - Jumbe, Phumelele (University of the Witwatersrand, Johannesburg, 2023)
Over the past several years, the rapid advancement of innovative technology has resulted in the expansion of electronic government (e-Government) practices as a novel paradigm for enhancing the provision of public services. Numerous governments worldwide are looking to capitalise on these advancements and see e-Government as a key driver of service efficiency and effectiveness. Unfortunately, e-Government implementation is complex and developing countries, in particular, face greater challenges than their counterparts. This places a greater burden on developing-country governments to develop better policies and strategies in order to facilitate the widespread e-Government uptake. This study investigated the critical factors affecting e-Government adoption in a developing country, South Africa. It used a hybrid TAM- UTAUT model, to explore the critical factors that drive the adoption of e-Government among South African citizens. The study addresses a gap in the e-Government literature in South Africa by presenting a model that government, policymakers, and administrators can employ to effectively expand the country's e-Government implementation program. The survey data collected from 238 respondents underwent analysis using the structural equation modelling (SEM) technique, with IBM SPSS tools utilized for the examination. This study revealed that Trust in e-Government, Performance Expectancy, Social Impact, Facilitating Conditions, Accessibility, and Perceived Enjoyment are pivotal factors influencing the adoption of e- Government among citizens in South Africa. While previous studies suggested age as a moderating variable between Performance Expectancy, Effort Expectancy, Social Impact, and the Behavioural Intention to Use e-Government Services, this study found that age does not act as a moderating variable among these factors. These findings contribute to theoretical understanding of how constructs commonly used in e-commerce can be applied to the e- Government setting, and can further assist the South African government and policymakers in developing effective e-Government policies to support the South African government's renewed approach and program, which aims to transform South African public service into an inclusive digital society where all citizens can reap the benefits of digital technology
A research report submitted in partial fulfillment of the requirements for the degree of Master of Commerce to the Faculty of Commerce, Law and Management, School of Business Sciences, , University of the Witwatersrand, Johannesburg, 2023
Keywords: Adoption; E-Government; TAM; Trust; UTAUT; Technology innovation; UCTD; SDG-11: Sustainable cities and communities